Analysis of Intrinsic Elements in the 2019 Earth Humans Film - Putri Utami, Endah; Fathurohman, Irfai; Roysa, Mila (Journal Sains and Education, 2024)
Intrinsic structure is the elements that build from within a literary work. Literary works such as in the form of films are basically built with intrinsic structural elements that include aspects such as theme, plot, characterization, setting, point of view, and morals. Based on the research conducted, there is a theme in the film Bumi Manusia, namely about the oppression of the Indigenous people by Europeans during the Dutch colonial era in the early twentieth century. This study uses a qualitative research type with a descriptive research nature and uses a literary sociology approach. The theory used in social values ??and moral values ??uses Roland Barthes' Semiotic theory by looking at the signifiers and signifieds which then become myths or meanings in the film Bumi Manusia. The main data obtained from the film Bumi Manusia, while additional data is obtained from novels, journals, theses, the internet that discuss films, social values ??and moral values. Data analysis is carried out by selecting signifiers and signifiers in the image so as to produce a meaning from the film and the final stage of this data analysis is to validate the data by increasing the rigidity and adequacy of references. The benefits of this study are 1) Theoretically (a) Can enrich the method of analyzing films, (b) Provides an overview of social values ??and moral values. 2) Practically (a) Can arouse the interest of students or teenagers to love and care for literary works more, (b) For teachers, can be used as a reference in selecting teaching materials, (c) For researchers can be used as a comparison and reference in conducting further research.